Nanometer SnO2-TiO2 heterojunction catalyst as well as preparation method and application thereof
Patent Information
- Application Number
- CN202411269506.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The current direct esterification method for preparing polyglycolic acid (PGA) has difficulty in obtaining products with high molecular weight and light color, low catalytic efficiency and residual tin catalysts, which limits the application of PGA.
Using nano SnO2-TiO2 heterojunction catalyst, defective mesoporous TiO2 is prepared by alcoholylation and hydrothermal reaction, and hydrothermal reaction is carried out in combination with tin compounds to reduce the use of metal Sn, improve catalytic activity, and achieve efficient catalytic synthesis of high molecular weight and Light color PGA.
It is realized that high-efficiency catalytic synthesis of high molecular weight and light color PGAs is reduced while reducing the amount of catalyst and energy consumption, thereby reducing product yellowing and improving reaction efficiency and product quality.
Smart Images

Figure CN119119448A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparing polyglycolic acid (PGA) by direct esterification, and in particular to a nano SnO2-TiO2 heterojunction catalyst particularly suitable for preparing polyglycolic acid (PGA) by direct esterification, and a preparation method and application thereof. Background Art
[0002] Polyglycolic acid (PGA) is an emerging highly crystalline semi-crystalline bio-friendly degradable polyester material with both biodegradability and biocompatibility. It plays an important role in biomedical fields such as surgical clinical medical sutures and tissue scaffolds. Its final degradation products in the body are water and carbon dioxide. Compared with polylactic acid (PLA), it has a faster degradation rate and better biocompatibility. When used in the body, it is beneficial to cell proliferation and cell adhesion. It has been widely used in medicine and is a biomedical material with good development prospects. Polyglycolic acid (PGA) has the advantages of excellent biocompatibility, mechanical properties, high barrier properties, high load deformation temperature, etc. It is a rare degradable engineering polymer material. Its biodegradability is similar to that of natural cellulose. At the same time, it meets the requirements of industrial composting, household composting and seawater degradation. It has been certified as a safe biodegradable plastic material in the United States, the European Union, Japan and other regions. It is widely used in high-end biomedicine, food packaging, shale and oil extraction and agricultural production, and has a broad market space.
[0003] At present, the synthesis methods of polyglycolic acid with industrial value include direct polycondensation and glycolide ring-opening polymerization. At present, the synthesis of PGA at home and abroad is mainly based on glycolide ring-opening polymerization, which has high requirements for the purity of glycolide and high product cost. It is mainly produced on a large scale in Japan and the United States.
[0004] In recent years, with the development of coal chemical technology and the breakthrough of key technology for preparing glycolic acid (methyl ester) from dimethyl oxalate at low cost, my country's PGA industry has brought important turning points and hope. The rapid growth of domestic glycolic acid monomer production scale and the reduction of costs make direct polymerization more likely to become the preferred solution for large-scale production of PGA in the future.
[0005] In terms of research on the direct synthesis of PGA, according to current patent and literature search analysis, there are 72 results (Scifinder search results) for the direct melt polymerization method for synthesizing PGA, but there is little reference information, only 11 references, and there is no report on the synthesis of high molecular weight (Mn>50000Da) light-colored PGA. In summary, the high technical difficulty of the direct esterification polymerization route has brought challenges and opportunities to the development of the entire industry.
[0006] The method of synthesizing PGA by direct polycondensation of glycolic acid is shorter and less expensive than the ring-opening polymerization of glycolide, and is more suitable for the production of bulk products. However, it is generally reported that this method is difficult to synthesize products with higher molecular weight and lighter color, which greatly limits the application of PGA. The direct esterification method often uses tin catalysts, such as stannous chloride dihydrate, stannous octoate, stannous chloride, tin oxide, etc. The low catalytic efficiency leads to a long reaction time, resulting in poor color of the polyglycolic acid product. If an excess of tin catalyst is used, it will usually remain in the polymer system and cannot be removed. Excessive tin catalyst residues will accelerate the degradation of polyglycolic acid. Summary of the invention
[0007] In view of the technical difficulty of obtaining high molecular weight and light color polyglycolic acid by direct esterification of glycolic acid in the prior art, the present invention provides a nano SnO2-TiO2 heterojunction catalyst particularly suitable for preparing polyglycolic acid by direct esterification of glycolic acid, and a preparation method and application thereof. The catalyst of the present invention is used for preparing polyglycolic acid by direct esterification of glycolic acid, and high molecular weight and light color high quality polyglycolic acid can be obtained.
[0008] To achieve the purpose, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing a nano SnO2-TiO2 heterojunction catalyst, comprising the following steps:
[0010] (1) alcoholyzing a titanium compound in a polyol, wherein the molar ratio of the titanium compound to the polyol is 0.001-0.5, and obtaining TiO2 nanoparticles through alcoholysis; then adding an alkali solution and an alcohol with a reducing potential, and performing a solvothermal reaction at 120-220° C., and then washing the obtained product, separating and drying it, to obtain defective mesoporous TiO2;
[0011] (2) Adding ammonia water dropwise to an aqueous solution of a tin compound heated to 35-80° C. until the pH value of the solution is 7-8, then adding the defective mesoporous TiO2 obtained in step (1) thereto, carrying out a hydrothermal reaction at 100-220° C., washing the obtained product, separating and drying it, and obtaining the catalyst.
[0012] In some embodiments, in step (1), the titanium compound is selected from one or more of tetrabutyl titanate, isopropyl titanate, cesium titanate, potassium titanate, titanyl sulfate, titanium tetrachloride, and titanium trichloride; preferably tetrabutyl titanate and / or titanium tetrachloride, more preferably titanium tetrachloride;
[0013] And / or, in step (1), the polyol is selected from one or more of propylene glycol, glycerol, ethylene glycol, butylene glycol, and pentanediol; preferably propylene glycol;
[0014] And / or, in step (1), the alcohol having a reducing potential is selected from one or more of n-butanol, 1,4-butanediol, 1,5-pentanediol, ethylene glycol, propylene glycol, and ethanol, preferably n-butanol.
[0015] In some embodiments, in step (1), the molar ratio of the titanium compound to the polyol is 0.005 to 0.1.
[0016] In some embodiments, in step (1), the alkali solution is an aqueous solution of an alkaline compound, and the alkaline compound is selected from one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide, aluminum hydroxide, potassium oxide, and potassium carbonate, preferably potassium hydroxide;
[0017] Preferably, the molar ratio of the alkaline compound in the alkali solution to the alcohol having a reducing potential is 0.01 to 0.2, and the molar ratio of the alkaline compound to the titanium compound is 5 to 0.5.
[0018] In some embodiments, the solvent thermal reaction time in step (1) is 2 to 24 hours;
[0019] And / or, in step (2), the hydrothermal reaction is carried out for 2-12 hours;
[0020] And / or, in step (1), the alcoholysis temperature is 15 to 220° C., and the alcoholysis time is 0.5 to 12 h.
[0021] In some embodiments, in step (2), the tin compound is selected from one or more of tin dichloride, tin tetrachloride, stannous oxalate, tin sulfide, and tin nitrate, preferably tin dichloride;
[0022] Preferably, the concentration of the tin compound aqueous solution is 0.05 mol / L to 0.5 mol / L.
[0023] In some embodiments, the molar ratio of the tin compound in step (2) to the titanium compound in step (1) is 0.01-0.5, preferably 0.01.
[0024] In some embodiments, in step (1), the particle size of the TiO2 nanoparticles is 5nm-20nm;
[0025] In step (2), the specific surface area of the catalyst is ≥50m 2 / g.
[0026] The present invention also provides a nano SnO2-TiO2 heterojunction catalyst prepared by the preparation method described above.
[0027] The present invention also provides the use of the nano SnO2-TiO2 heterojunction catalyst described above in the preparation of polyglycolic acid; preferably, the application is the use of the catalyst in the preparation of the polyglycolic acid by direct esterification using glycolic acid as a raw material.
[0028] The technical solution provided by the present invention has the following beneficial effects:
[0029] The nano SnO2-TiO2 heterojunction catalyst prepared by the preparation method of the present invention has an excellent catalytic effect in the reaction of preparing polyglycolic acid by direct esterification and polycondensation of glycolic acid, and can obtain polyglycolic acid with high molecular weight and light color. The synergistic catalysis of SnO2 and nano TiO2 in the catalyst can play a high catalytic activity when the amount of catalyst is reduced, especially when the amount of metal Sn is reduced, which is conducive to effectively reducing the reaction time, reducing energy consumption, inhibiting yellowing of the product, and realizing efficient catalytic synthesis of PGA. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the EPR characterization result of defective mesoporous TiO2 in Preparation Example 1.
[0031] Figure 2 Electron microscope photo of 0.05Sn-TiO2-B prepared in Preparation Example 1 DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.
[0034] The present invention provides a method for preparing a nano SnO2-TiO2 heterojunction catalyst, comprising the following steps:
[0035] (1) A titanium compound is subjected to alcoholysis in a polyol, wherein the molar ratio of the titanium compound to the polyol is 0.001-0.5, and TiO2 nanoparticles are obtained by alcoholysis; then, an alkali solution and an alcohol with a reducing potential are added, and a solvothermal reaction is carried out at 120-220°C, and then the obtained product is washed, separated and dried to obtain defective mesoporous TiO2; specifically, the washing can be carried out by washing with anhydrous ethanol; the separation can be centrifugal separation, and the drying can be vacuum drying.
[0036] (2) Adding ammonia water dropwise to a tin compound aqueous solution heated to 35-80° C. until the pH value of the solution is 7-8, then adding the defective mesoporous TiO2 obtained in step (1) thereto, performing a hydrothermal reaction at 100-220° C., washing the obtained product, separating and drying it to obtain a catalyst, which is a nano SnO2-TiO2 heterojunction catalyst. Specifically, the washing can be washing with anhydrous ethanol; the separation can be centrifugal separation; and the drying can be vacuum drying.
[0037] The nano SnO2-TiO2 heterojunction catalyst prepared by the preparation method of the present invention has an excellent catalytic effect in the reaction of preparing polyglycolic acid by direct esterification and polycondensation of glycolic acid, and can obtain polyglycolic acid with high molecular weight and light color. The synergistic catalysis of SnO2 and nano TiO2 in the catalyst can exert high catalytic activity under the condition of reducing the amount of catalyst, especially reducing the amount of metal Sn, which is conducive to effectively reducing the reaction time, reducing energy consumption, inhibiting yellowing of the product, and realizing efficient catalytic synthesis of PGA.
[0038] In some embodiments, in step (1), the titanium compound is selected from one or more of tetrabutyl titanate, isopropyl titanate, cesium titanate, potassium titanate, titanyl sulfate, titanium tetrachloride, and titanium trichloride; preferably tetrabutyl titanate and / or titanium tetrachloride, more preferably titanium tetrachloride. Using titanium tetrachloride as the preferred titanium compound is conducive to obtaining a catalyst with better catalytic performance, which is not only conducive to the preparation of high molecular weight polyglycolic acid, but also conducive to obtaining a product with lighter color.
[0039] In some embodiments, in step (1), the polyol is selected from one or more of propylene glycol, glycerol, ethylene glycol, butylene glycol, and pentanediol; preferably propylene glycol. The use of the preferred polyol is conducive to obtaining a catalyst with better catalytic performance.
[0040] In a preferred embodiment, in step (1), the alcohol with weak reduction potential is selected from one or more of n-butanol, 1,4-butanediol, 1,5-pentanediol, ethylene glycol, propylene glycol, and ethanol, preferably n-butanol; using the preferred alcohol with reduction potential is conducive to obtaining a catalyst with better catalytic performance.
[0041] In step (1), the molar ratio of the titanium compound to the polyol is 0.001-0.5. In step (1), the titanium compound and the polyol in the above molar ratio are used to obtain monodisperse TiO2 nanoparticles of 5-20nm. The alcoholysis rate can be adjusted by adjusting the titanium alcohol ratio, thereby obtaining catalysts with different catalytic activity levels. Preferably, the molar ratio of the titanium compound to the polyol is 0.005-0.1, for example 0.01. By using the preferred molar ratio, a catalyst with better catalytic performance can be obtained. Under the condition that other conditions are basically the same, it is conducive to better balancing the preparation of high molecular weight and light color polyglycolic acid.
[0042] In some embodiments, in step (1), the alkali solution is an aqueous solution of an alkaline compound, the concentration of the alkali solution is, for example, 2 to 25 wt %, and the alkaline compound is selected from one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide, aluminum hydroxide, potassium oxide, and potassium carbonate, preferably potassium hydroxide. The use of a preferred alkaline compound is conducive to obtaining a catalyst with better catalytic performance.
[0043] In some embodiments, the molar ratio of the alkaline compound in the alkali solution to the alcohol having a reducing potential is 0.01 to 0.2, and the molar ratio of the alkaline compound to the titanium compound is 5 to 0.5.
[0044] In some embodiments, the solvent thermal reaction time in step (1) is 2 to 24 hours;
[0045] In some embodiments, in step (2), the hydrothermal reaction is carried out for 2-12 hours;
[0046] In some embodiments, in step (1), the alcoholysis temperature is 15 to 220° C., and the alcoholysis time is 0.5 to 12 h.
[0047] In some embodiments, in step (2), the tin compound is selected from one or more of tin dichloride, tin tetrachloride, stannous oxalate, tin sulfide, and tin nitrate, preferably tin dichloride, which is conducive to the preparation of polyglycolic acid with better balance of high molecular weight and light color under other conditions being substantially the same;
[0048] Preferably, the concentration of the tin compound aqueous solution is 0.05 mol / L to 0.5 mol / L.
[0049] In some embodiments, the molar ratio of the tin compound in step (2) to the titanium compound in step (1) is 0.01-0.5, preferably 0.01.
[0050] In the preparation method of the present invention, TiO2 nanoparticles with a particle size of 5nm-20nm can be obtained in step (1); and TiO2 nanoparticles with a specific surface area of ≥50m can be obtained in step (2). 2 / g of nano SnO2-TiO2 heterojunction catalyst.
[0051] The present invention also provides a nano SnO2-TiO2 heterojunction catalyst prepared by the preparation method described above.
[0052] The present invention also provides the use of the nano SnO2-TiO2 heterojunction catalyst described above in the preparation of polyglycolic acid; preferably, the catalyst is used in the preparation of the polyglycolic acid by direct esterification using glycolic acid as a raw material.
[0053] The present invention is further described below by way of examples, but it should not be understood that the present invention is limited thereto.
[0054] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0055] The detection methods involved in the following embodiments are described as follows:
[0056] b value: colorimetric analysis was performed using a colorimeter, referring to GB / T 14190-2017. Particle size of TiO2 nanoparticles: characterized by transmission electron microscopy. Specific surface area of the catalyst: isothermal N2 adsorption and desorption test.
[0057] Preparation Example 1
[0058] A nano SnO2-TiO2 heterojunction catalyst is prepared according to the following method:
[0059] (1) At room temperature, add titanium tetrachloride and propylene glycol in a molar ratio of 1:100 to a three-necked flask and stir for 1 hour to obtain monodisperse TiO2 nanoparticles (particle size 5nm); then add alkali solution and n-butanol (the alkali solution is a 5wt% potassium hydroxide aqueous solution, the molar ratio of potassium hydroxide to n-butanol is 0.05, and the molar ratio of potassium hydroxide to titanium tetrachloride is 1); start heating, heat to 160°C for 2 hours, wash the product with anhydrous ethanol, centrifuge, and vacuum dry to obtain defective mesoporous TiO2. The obtained product was characterized by EPR, and the results are shown in Figure 1 , Figure 1 The characteristic signal peak at g = 2.003 is the characteristic signal peak of oxygen vacancies capturing single electrons, which indicates that the obtained mesoporous TiO2 has oxygen vacancy defects.
[0060] (2) A 0.05 mol / L aqueous solution of tin dichloride (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) is 0.05) is heated to 50° C., and ammonia water is added dropwise until the pH value of the solution is 7-8. During the process of adding ammonia water, the tin dichloride is gradually hydrolyzed to obtain a nano-tin oxide SnO2 dispersion. The defective mesoporous TiO2 prepared above is added to the dispersion, and a hydrothermal reaction is carried out at 150° C. for 3 h. The product is washed with anhydrous ethanol, centrifuged, and vacuum dried to obtain a catalyst 0.05Sn-TiO2-B with a specific surface area of 320 m 2 / g, SEM photos are attached Figure 2 , size (diameter) is about 200nm.
[0061] Preparation Example 2
[0062] A nano SnO2-TiO2 heterojunction catalyst is prepared according to the following method:
[0063] (1) At room temperature, titanium tetrachloride and propylene glycol in a molar ratio of 1:100 are added to a three-necked flask and stirred for 6 hours to obtain monodisperse TiO2 nanoparticles (particle size is 20 nm); then alkali solution and n-butanol are added (the alkali solution is a 10% potassium hydroxide aqueous solution, the molar ratio of potassium hydroxide to n-butanol is 0.1, and the molar ratio of potassium hydroxide to titanium tetrachloride is 2); heating is started and heated to 130°C for 2 hours. The product is washed with anhydrous ethanol, centrifuged and vacuum dried to obtain defective mesoporous TiO2.
[0064] (2) A 0.1 mol / L aqueous solution of tin dichloride (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) is 0.1) is heated to 50° C., and ammonia water is added dropwise until the pH value of the solution is 7-8. During the process of adding ammonia water, the tin dichloride is gradually hydrolyzed to obtain a nano-tin oxide SnO2 dispersion. The defective mesoporous TiO2 prepared above is added to the dispersion, and a hydrothermal reaction is carried out at 150° C. for 3 h. The product is washed with anhydrous ethanol, centrifuged, and vacuum dried to obtain a catalyst 0.1Sn-TiO2-B with a specific surface area of 285 m 2 / g, and the size is about 220nm.
[0065] Preparation Example 3 (Compared with Preparation Example 1, the polyol used is butanediol)
[0066] A nano SnO2-TiO2 heterojunction catalyst is prepared according to the following method:
[0067] (1) At room temperature, titanium tetrachloride and butanediol in a molar ratio of 1:100 are added to a three-necked flask and stirred for 1 hour to obtain monodisperse TiO2 nanoparticles (particle size is 10 nm); then alkali solution and n-butanol are added (the alkali solution is a 5 wt% potassium hydroxide aqueous solution, the molar ratio of potassium hydroxide to n-butanol is 0.05, and the molar ratio of potassium hydroxide to titanium tetrachloride is 1); heating is started and heated to 130°C for 2 hours. The product is washed with anhydrous ethanol, centrifuged and vacuum dried to obtain defective mesoporous TiO2.
[0068] (2) A 0.05 mol / L aqueous solution of tin dichloride (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) is 0.05) is heated to 50° C., and ammonia water is added dropwise until the pH value of the solution is 7-8. During the process of adding ammonia water, the tin dichloride is gradually hydrolyzed to obtain a nano-tin oxide SnO2 dispersion. The defective mesoporous TiO2 prepared above is added to the dispersion, and a hydrothermal reaction is carried out at 150° C. for 3 h. The product is washed with anhydrous ethanol, centrifuged, and vacuum dried to obtain a catalyst 0.05Sn-TiO2-D with a specific surface area of 450 m 2 / g, and the size is about 260nm.
[0069] Preparation Example 4 (Compared with Preparation Example 1, the molar ratio of potassium hydroxide to n-butanol is different)
[0070] A nano SnO2-TiO2 heterojunction catalyst is prepared according to the following method:
[0071] (1) At room temperature, titanium tetrachloride and propylene glycol in a molar ratio of 1:100 are added to a three-necked flask and stirred for 1 hour to obtain monodisperse TiO2 nanoparticles (particle size is 5 nm); then alkali solution and n-butanol are added (the alkali solution is a 5 wt% potassium hydroxide aqueous solution, the molar ratio of potassium hydroxide to n-butanol is 0.2, and the molar ratio of potassium hydroxide to titanium tetrachloride is 1); heating is started and heated to 130°C for 2 hours. The product is washed with anhydrous ethanol, centrifuged and vacuum dried to obtain defective mesoporous TiO2.
[0072] (2) A 0.05 mol / L aqueous solution of tin dichloride (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) is 0.05) is heated to 50° C., and ammonia water is added dropwise until the pH value of the solution is 7-8. During the process of adding ammonia water, the tin dichloride is gradually hydrolyzed to obtain a nano-tin oxide SnO2 dispersion. The defective mesoporous TiO2 prepared above is added to the dispersion, and a hydrothermal reaction is carried out at 150° C. for 3 h. The product is washed with anhydrous ethanol, centrifuged, and vacuum dried to obtain a catalyst 0.05Sn-TiO2-0.2 with a specific surface area of 355 m 2 / g, and the size is about 80nm.
[0073] Preparation Example 5 (Compared with Preparation Example 1, the hydrothermal reaction time is prolonged)
[0074] A nano SnO2-TiO2 heterojunction catalyst is prepared according to the following method:
[0075] (1) At room temperature, titanium tetrachloride and propylene glycol in a molar ratio of 1:100 are added to a three-necked flask and stirred for 1 hour to obtain monodisperse TiO2 nanoparticles (particle size of 5 nm); then alkali solution and n-butanol are added (the alkali solution is a 5% potassium hydroxide aqueous solution, the molar ratio of potassium hydroxide to n-butanol is 0.05, and the molar ratio of potassium hydroxide to titanium tetrachloride is 1); heating is started and heated to 130°C for 2 hours. The product is washed with anhydrous ethanol, centrifuged and vacuum dried to obtain defective mesoporous TiO2.
[0076] (2) A 0.05 mol / L aqueous solution of tin dichloride (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) is 0.05) is heated to 50° C., and ammonia water is added dropwise until the pH value of the solution is 7-8. During the process of adding ammonia water, the tin dichloride is gradually hydrolyzed to obtain a nano-tin oxide SnO2 dispersion. The defective mesoporous TiO2 prepared above is added to the dispersion, and a hydrothermal reaction is carried out at 150° C. for 6 h. The product is washed with anhydrous ethanol, centrifuged, and vacuum dried to obtain a catalyst 0.05Sn-TiO2-6h with a specific surface area of 510 m 2 / g, and the size is about 180nm.
[0077] Example 1
[0078] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-B obtained in Preparation Example 1 as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.05% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification was carried out at 190° C. for 1.5 h, and the condensation reaction was stopped at 220° C. for 2 h to obtain the product PGA1. The obtained product was subjected to GPC (gel permeation chromatography) test and color value test. The test results are shown in Table 1.
[0079] Example 2 (Compared with Example 1, the amount of catalyst is increased)
[0080] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-B obtained in Preparation Example 1 as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.1% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification reaction was carried out at 190° C. for 1.5 h, and the condensation reaction was stopped at 220° C. for 2 h to obtain the product PGA2. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0081] Example 3
[0082] Using 0.1 mol of glycolic acid as a raw material and 0.1Sn-TiO2-B obtained in Preparation Example 2 as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.05% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification reaction was carried out at 190° C. for 1.5 h, and the condensation reaction was stopped at 220° C. for 2 h to obtain the product PGA3. The obtained product was subjected to GPC and color value tests. The test results are shown in Table 1.
[0083] Example 4
[0084] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-D obtained in Preparation Example 3 as a catalyst, the amount of the catalyst (measured as titanium dioxide) was 0.05% by mole of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification was carried out at 190° C. for 1.5 h, and the condensation reaction was stopped at 220° C. for 2 h to obtain the product PGA4. The obtained product was subjected to GPC and color value tests. The test results are shown in Table 1.
[0085] Example 5
[0086] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-0.2 obtained in Preparation Example 4 as a catalyst, the amount of the catalyst (measured as titanium dioxide) was 0.05% by mole of glycolic acid, and the esterification reaction was carried out under nitrogen protection, esterification at 190°C for 1.5h, and condensation reaction at 220°C for 2h to stop the reaction, to obtain the product PGA5. The obtained product was subjected to GPC and color value tests, and the test results are shown in Table 1.
[0087] Example 6
[0088] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-6h obtained in Preparation Example 5 as a catalyst, the amount of the catalyst (measured as titanium dioxide) was 0.05% of the molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification was carried out at 190°C for 1.5 hours, and the condensation reaction was stopped at 220°C for 2 hours to obtain the product PGA6. The obtained product was subjected to GPC and color value tests. The test results are shown in Table 1.
[0089] Example 7 (Compared with Example 1, the molar ratio of titanium tetrachloride to propylene glycol is 0.001)
[0090] The catalyst used in Example 7 was prepared in accordance with Example 1, except that the catalyst used was different. The catalyst used in Example 7 was prepared in accordance with Example 1. The difference from Example 1 was that in step (1), the molar ratio of titanium tetrachloride to propylene glycol was 0.001, and the catalyst 0.05Sn-TiO2 (0.001) was obtained. The specific surface area of the catalyst finally obtained was 335m 2 / g, and the size is about 190nm.
[0091] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2 (0.001) as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.05% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification was carried out at 190°C for 1.5 h, and the condensation reaction was stopped at 220°C for 2 h to obtain the product PGA7. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0092] Example 8 (Compared with Example 1, the molar ratio of titanium tetrachloride to propylene glycol is 0.1)
[0093] The catalyst used in Example 8 was prepared in accordance with Example 1, except that the catalyst used was different. The catalyst used in Example 8 was prepared in accordance with Example 1. The difference from Example 1 was that in step (1), the molar ratio of titanium tetrachloride to propylene glycol was 0.1, and the catalyst 0.05Sn-TiO2 (0.1) was obtained. The specific surface area of the catalyst finally obtained was 205m 2 / g, and the size is about 305nm.
[0094] Using 0.1 mol of glycolic acid as raw material and 0.05Sn-TiO2 (0.1) as catalyst, the amount of catalyst (measured in titanium dioxide) was 0.1% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection, esterification at 190°C for 1.5h, and condensation reaction at 220°C for 2h to stop the reaction, to obtain the product PGA8. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0095] Example 9 (Compared with Example 1, titanium tetrachloride was replaced with tetrabutyl titanate)
[0096] The catalyst used in Example 9 was prepared in accordance with Example 1, except that the catalyst used was different. The catalyst used in Example 9 was prepared in accordance with Example 1. The difference from Example 1 was that in step (1), titanium tetrachloride was replaced with tetrabutyl titanate, and the heating reaction temperature was 150°C to obtain the catalyst 0.05Sn-TiO2-TBOT. The specific surface area of the catalyst finally obtained was 255m 2 / g, and the size is about 210nm.
[0097] Using 0.1 mol of glycolic acid as a raw material, and 0.05Sn-TiO2-TBOT obtained in Preparation Example 1 as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.05% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection, esterification at 190°C for 1.5h, and condensation reaction at 220°C for 2h to stop the reaction, to obtain the product PGA9. The obtained product was subjected to GPC test and color value test, and the test results are shown in Table 1.
[0098] Example 10 (Compared with Example 1, tin dichloride is replaced by stannous oxalate)
[0099] The catalyst used in Example 10 was prepared in accordance with Example 1, except that the catalyst used was different. The catalyst used in Example 10 was prepared in accordance with Example 1, and the difference from Example 1 was that in step (2), tin dichloride was replaced with stannous oxalate to obtain the catalyst 0.05Sn-TiO2-oxa. The specific surface area of the catalyst finally obtained was 380 m 2 / g, and the size is about 155nm.
[0100] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-oxa obtained in Preparation Example 1 as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.05% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification reaction was carried out at 190° C. for 1.5 h, and the condensation reaction was stopped at 220° C. for 2 h to obtain the product PGA10. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0101] Example 11 (Compared with Example 1, potassium hydroxide is replaced by sodium hydroxide)
[0102] The catalyst used in Example 1 was prepared in accordance with Example 1, except that the catalyst used was different. The catalyst used in Example 11 was prepared in accordance with Example 1. The difference from Example 1 was that in step (1), potassium hydroxide was replaced with sodium hydroxide to obtain a catalyst 0.05Sn-TiO2-Na. The specific surface area of the catalyst finally obtained was 330 m 2 / g, and the size is about 185nm.
[0103] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-Na obtained in Preparation Example 1 as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.05% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification was carried out at 190° C. for 1.5 h, and the condensation reaction was stopped at 220° C. for 2 h to obtain the product PGA11. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0104] Example 12 (Compared with Example 1, the reaction temperature of step (1) was adjusted from 160°C to 120°C)
[0105] The catalyst used in Example 12 was prepared in accordance with Example 1, except that the catalyst used was different. The catalyst used in Example 12 was prepared in accordance with Example 1. The difference from Example 1 was that in step (1), the heating reaction temperature was adjusted from 160°C to 120°C to obtain the catalyst 0.05Sn-TiO2-120. The specific surface area of the catalyst finally obtained was 265m 2 / g, and the size is about 160nm.
[0106] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-120 obtained in Preparation Example 1 as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.05% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification reaction was carried out at 190°C for 1.5 hours, and the condensation reaction was stopped at 220°C for 2 hours to obtain the product PGA12. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0107] Example 13 (Compared with Example 1, the reaction temperature of step (2) was adjusted from 150°C to 100°C)
[0108] The catalyst used in Example 13 was prepared in accordance with Example 1, except that the catalyst used was different. The catalyst used in Example 13 was prepared in accordance with Example 1. The difference from Example 1 was that in step (2), the hydrothermal reaction temperature was adjusted from 150°C to 100°C to obtain the catalyst 0.05Sn-TiO2-100. The specific surface area of the catalyst finally obtained was 325m 2 / g, and the size is about 210nm.
[0109] Using 0.1 mol of glycolic acid as a raw material and 0.05Sn-TiO2-100 obtained in Preparation Example 1 as a catalyst, the amount of the catalyst (measured in terms of titanium dioxide) was 0.05% molar amount of glycolic acid, and the esterification reaction was carried out under nitrogen protection. The esterification reaction was carried out at 190°C for 1.5 hours, and the condensation reaction was stopped at 220°C for 2 hours to obtain the product PGA13. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0110] Comparative Example 1
[0111] Using 0.1 mol of glycolic acid as a raw material and commercial stannous octoate as a catalyst in an amount of 0.05% molar amount of glycolic acid, the esterification reaction was carried out under nitrogen protection, esterification was carried out at 190° C. for 1.5 h, and the condensation reaction was stopped at 220° C. for 2 h to obtain the product PGAD1. The obtained product was subjected to GPC and color value tests. The test results are shown in Table 1.
[0112] Comparative Example 2 (Compared with Comparative Example 1, the amount of catalyst was increased)
[0113] Using 0.1 mol of glycolic acid as a raw material and commercial stannous octoate as a catalyst in an amount of 0.08% molar amount of glycolic acid, the esterification reaction was carried out under nitrogen protection, esterification was carried out at 190° C. for 1.5 h, and the condensation reaction was stopped at 220° C. for 2 h to obtain the product PGAD2. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0114] Comparative Example 3
[0115] Using 0.1 mol of glycolic acid as a raw material and commercial titanium dioxide P25 as a catalyst in an amount of 0.05% molar amount of glycolic acid, the esterification reaction was carried out under nitrogen protection, esterification was carried out at 190°C for 1.5 h, and the condensation reaction was stopped at 220°C for 2 h to obtain the product PGAD3. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.
[0116] Comparative Example 4 (Compared with Comparative Example 3, the amount of catalyst was increased)
[0117] Using 0.1 mol of glycolic acid as raw material and commercial titanium dioxide P25 as catalyst, the dosage is 0.08% molar amount of glycolic acid, and the esterification reaction is carried out under nitrogen protection, esterification at 190°C for 1.5h, and condensation reaction at 220°C for 2h to stop the reaction, to obtain the product PGAD4. The obtained product is subjected to GPC and color value tests. The test results are shown in Table 1.
[0118] Table 1 GPC and b value test results of prepared PGA
[0119]
[0120] The results show that the nano SnO2-TiO2 heterojunction catalyst prepared by the present invention has the following advantages compared with the traditional polyester catalyst:
[0121] 1) Low preparation cost, high catalytic activity and good stability;
[0122] 2) Doping with a small amount of Sn can still achieve good catalytic effect when reducing the amount of catalyst, especially reducing the amount of Sn;
[0123] 3) The catalyst prepared by the preparation method of the present invention can adjust the morphology and size of defective mesoporous TiO2 by adjusting the material ratio, reaction conditions, raw material types, etc., and the catalyst activity can be controlled, which can effectively reduce the lactide content and inhibit other side reactions, and can produce high molecular weight PGA. The prepared PGA has high quality, good color, and low b value. The use of the catalyst of the present invention is conducive to improving the reaction efficiency of preparing polyglycolic acid (PGA) by direct esterification, shortening the reaction time, thereby reducing energy consumption, and has the effect of inhibiting product yellowing.
[0124] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A method for preparing a nano SnO2-TiO2 heterojunction catalyst, characterized in that: The steps include: (1) alcoholyzing a titanium compound in a polyol, wherein the molar ratio of the titanium compound to the polyol is 0.001-0.5, and obtaining TiO2 nanoparticles through alcoholysis; then adding an alkali solution and an alcohol with a reducing potential, and performing a solvothermal reaction at 120-220° C., and then washing the obtained product, separating and drying it, to obtain defective mesoporous TiO2; (2) Adding ammonia water dropwise to an aqueous solution of a tin compound heated to 35-80° C. until the pH value of the solution is 7-8, then adding the defective mesoporous TiO2 obtained in step (1) thereto, carrying out a hydrothermal reaction at 100-220° C., washing the obtained product, separating and drying it, and obtaining the catalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the titanium compound is selected from one or more of tetrabutyl titanate, isopropyl titanate, cesium titanate, potassium titanate, titanyl sulfate, titanium tetrachloride, and titanium trichloride; preferably tetrabutyl titanate and / or titanium tetrachloride, more preferably titanium tetrachloride; And / or, in step (1), the polyol is selected from one or more of propylene glycol, glycerol, ethylene glycol, butylene glycol, and pentanediol; preferably propylene glycol; And / or, in step (1), the alcohol having a reducing potential is selected from one or more of n-butanol, 1,4-butanediol, 1,5-pentanediol, ethylene glycol, propylene glycol, and ethanol, preferably n-butanol.
3. The preparation method according to any one of claims 1 to 2, characterized in that: In step (1), the molar ratio of the titanium compound to the polyol is 0.005 to 0.
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step (1), the alkali solution is an aqueous solution of an alkaline compound, and the alkaline compound is selected from one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide, aluminum hydroxide, potassium oxide, and potassium carbonate, preferably potassium hydroxide; Preferably, the molar ratio of the alkaline compound in the alkali solution to the alcohol having a reducing potential is 0.01 to 0.2, and the molar ratio of the alkaline compound to the titanium compound is 5 to 0.
5.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The solvent thermal reaction time in step (1) is 2 to 24 hours; And / or, in step (2), the hydrothermal reaction is carried out for 2-12 hours; And / or, in step (1), the alcoholysis temperature is 15 to 220° C., and the alcoholysis time is 0.5 to 12 h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (2), the tin compound is selected from one or more of tin dichloride, tin tetrachloride, stannous oxalate, tin sulfide, and tin nitrate, preferably tin dichloride; Preferably, the concentration of the tin compound aqueous solution is 0.05 mol / L to 0.5 mol / L.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The molar ratio of the tin compound in step (2) to the titanium compound in step (1) is 0.01-0.5, preferably 0.
01.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (1), the particle size of the TiO2 nanoparticles is 5nm-20nm; In step (2), the specific surface area of the catalyst is ≥50m 2 / g.
9. A nano SnO2-TiO2 heterojunction catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the nano SnO2-TiO2 heterojunction catalyst according to claim 9 in the preparation of polyglycolic acid; preferably, the application is the use of the catalyst in the preparation of the polyglycolic acid by direct esterification using glycolic acid as a raw material.
